An Obituary-Brigadier Chiragh Hassan Breathes his Last - Muzaffar, Muhammad (Pakistan Armed Forces Medical Journal, 2023)
An eminent senior Pathologist, Brigadier Chiragh Hassan, died in Lahore on 20th October 2022. He wasborn in the Hoshiarpur District and migrated to Lyallpur in 1947.He graduated from King Edward Medical College,Lahore in 1961; had a span of government service, firstas House Physician in Mayo Hospital and later asRegistrar till September 1965. He volunteered for thearmed services in the 1965 war, where he continued toserve till his retirement as Brigadier from CombinedMilitary Hospital, Lahore Pakistan. He did his FCPS in1978 and proceeded to on-the-job training in Tumor Pathology in a specialist unit in London for about a year.He spent a considerable part of his service at Pakistan Naval Ship, Shifa Hospital and did an excellent job in upgrading its laboratory.Dr Chiragh was a keen tennis player. He was very hospitable and loved by his friends and family alike. After retirement, he was an honorary consultantin a Lahore laboratory run by a Non-GovernmentOrganizations (NGO) in Lahore Cantt, Pakistan. The profession will be the loser with the departureof Brigadier Dr Chiragh.May Allah bless the soul!